The effect of teff seed on hematological findings and anthropometric measurements - Geçgil Demir, Eftal; Tarakçı, Nadide Gizem; Samancı, Ruken Aslınur; Cambaz, Merve; Bilici, Şeymanur; Tuygan, Dilara; Çalık, Büşra; Çiftçi, Ayşe Sümeyye (NLM (Medline), 2022)
Background: The low incidence of diseases such as celiac, anemia, osteoporosis, and obesity in Ethiopia has aroused interest in the study of teff. The primary objective of this study was to determine the effect of regular consumption of teff seeds on hematological findings and anthropometric measurements in overweight and obese individuals. The secondary objective was to compare these effects of teff seeds with the Mediterranean diet. Methods: In our study, planned as a cohort study, 28 participants followed the teff seed-containing diet (n=14) and the Mediterranean diet (n=14) for 3 months. To determine nutritional status, a 72-h recall was taken. Anthropometric measurements and hematological findings were recorded at the beginning and end of the study. Results: There was a significant decrease in fasting blood glucose, cholesterol, LDL, and HDL levels in the teff group (p<0.05). The increase in total protein levels in the teff group was significantly higher than in the Mediterranean diet group (p=0.05). With increased intake of carbohydrates (g) in the teff group, fasting blood glucose levels decreased significantly. There was no significant difference between the two groups regarding anthropometric measurements. Conclusion: It has been found that the teff seed has no predominance over anthropometric measurements, as compared to the Mediterranean diet, and that it is more effective in improving hematological findings related to obesity. There is a need for more comprehensive studies that also address physical activity, the different types of teff seeds available, and include increased participant numbers.
Keywords: Teff Seeds; Mediterranean Diet; Obesity; Hematological Findings; Anthropometric Measurements